2017
DOI: 10.1016/j.gca.2016.12.034
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating zinc isotope fractionation under sulfate reducing conditions using a flow-through cell and in situ XAS analysis

Abstract: A flow-through cell experiment was conducted to evaluate Zn isotope fractionation during ZnS precipitation under microbially-mediated sulfate-reducing conditions. Synthetic groundwater containing 0.90 mM Zn was pumped through a cell containing creek sediment that was biostimulated to promote sulfate reducing conditions. Real-time, in situ X-ray absorption spectroscopy (XAS) was applied at the Zn K-edge to collect spectra via a Kapton window in the front of the cell over the course of the experiment. Aqueous ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 42 publications
3
13
0
Order By: Relevance
“…However, other lower δ 66 Zn values of our shales precipitated from ferruginous condition could indicate Zn isotope fractionation between Zn sulfides and the water column. In this case, the average δ 66 Zn value of deep water may be close to 0.5‰, based on the average δ 66 Zn bulk value (0.23‰) of our shales and the previous observed Zn isotope fractionation between sulfide and solution with Δ 66 Zn sulfide‐solution = ~−0.3‰ (Archer & Vance, ; Jamieson‐Hanes et al, ; Veeramani et al, ).…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…However, other lower δ 66 Zn values of our shales precipitated from ferruginous condition could indicate Zn isotope fractionation between Zn sulfides and the water column. In this case, the average δ 66 Zn value of deep water may be close to 0.5‰, based on the average δ 66 Zn bulk value (0.23‰) of our shales and the previous observed Zn isotope fractionation between sulfide and solution with Δ 66 Zn sulfide‐solution = ~−0.3‰ (Archer & Vance, ; Jamieson‐Hanes et al, ; Veeramani et al, ).…”
Section: Discussionsupporting
confidence: 78%
“…However, other lower δ 66 Zn values of our shales precipitated from ferruginous condition could indicate Zn isotope fractionation between Zn sulfides and the water column. In this case, the average δ 66 Zn value of deep water may be close to 0.5‰, based on the average δ 66 Zn bulk value (0.23‰) of our shales and the previous observed Zn isotope fractionation between sulfide and solution with Δ 66 Zn sulfide-solution =~À0.3‰ (Archer & Vance, 2004;Jamieson-Hanes et al, 2017;Veeramani et al, 2015). Scott et al (2013) proposed that the Zn concentration in seawater was broadly uniform over time and has maintained near-modern levels that were several orders of magnitude above the biolimiting concentration, which has been confirmed by other investigations regarding Zn concentrations and Zn/Fe ratios in banded iron formation (Robbins et al, , 2016.…”
Section: 1029/2018jc014068supporting
confidence: 78%
See 1 more Smart Citation
“…Zn sulfides are isotopically lighter compared to other mineral phases (John et al, 2008;Kelley et al, 2009;Veeramani et al, 2015;Jamieson-Hanes et al, 2017) and Aucour and co-workers (2016) found enrichment of light Zn isotopes in roots compared to the soil in a wetland system in France, due to the dissolution of ZnS enriched in light isotopes.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The changes in sedimentary mineralogy induced by diagenetic processes, tidal cycles and bioturbation affects the Zn mobility in the sediment/water interface and its isotope compositions (Veeramani et al, 2015;Jamieson-Hanes et al, 2017, Deckov et al, 2010. A flow-through cell experiment designed for the study of Zn speciation in situ in natural sediments demonstrated an enrichment of the heavier Zn isotope in the aqueous phase due to the continuous Zn removal via microbially-mediated ZnS precipitation in reducing conditions (Jamieson-Hanes et al, 2017). Leaching experiments of metallurgical slags showed different directions and extent of Zn isotope fractionation depending on the formation or dissolution of secondary phases such as carbonates, hydroxides, or oxides during weathering (Yin et al, 2018).…”
Section: Accepted Manuscriptmentioning
confidence: 99%